Practical aspects of developing genetic resistance to trypanosomiasis - Trail, J.C.M.; D'Ieteren, G.D.M.; Murray, M. (CAB International, 1991)
This paper reviews studies on the relationships between trypanotolerance and performance of cattle, and the genetics of trypanotolerance traits. Results of these studies are used to discuss the practical possibilities of increasing trypanotolerance through selection.